CGRP/CGRP Receptor Antibodies: Potential Adverse Effects Due to Blockade of Neovascularization?. (January 2019) - Majima, Masataka; Ito, Yoshiya; Hosono, Kanako; Amano, Hideki
Abstract : Migraine is a severe neurological disorder in which calcitonin gene-related peptide (CGRP) is a key molecule in pathophysiology. Neuronal system-derived CGRP enhances neovascularization in several important pathological conditions and sends a cue to the vascular system. In 2018, the FDA approved erenumab and fremanezumab, antibodies against CGRP receptor and CGRP, as the first new class of drugs for migraine. Treatment of migraine with these antibodies requires great care because neovascularization-related adverse effects may be induced in some patients. Here, we focus on enhancement of neovascularization by CGRP and discuss possible adverse effects resulting from blocking neovascularization. We also suggest that CGRP antibodies may also be used as novel antitumor agents by suppressing tumor-associated angiogenesis. Highlights: Vasodilating calcitonin gene-related peptide (CGRP), a key neuropeptide in migraine pathophysiology, exhibits proangiogenic and prolymphangiogenic activities. It also sends a cue for neovascularization to modulate recovery from ischemia, healing ulcers and wounds, and lymph edema, and to enhance tumor-associated angiogenesis and tumor growth. In 2018, the FDA approved CGRP/CGRP receptor antibodies that prevent migraine, representing progress over simple relief therapeutics. Long-term administration of CGRP/CGRP receptor antibodies could possibly induce adverse effects related to suppression of neovascularization. CGRP/CGRP receptor antibodies could also suppress tumor-associated angiogenesis. Therapeutic benefits versus neovascularization-related adverse effects from CGRP antibodies should be carefully evaluated over a long-term clinical trial.